2017
DOI: 10.1093/jeea/jvx037
|View full text |Cite
|
Sign up to set email alerts
|

War, Migration and the Origins of the Thai Sex Industry

Abstract: This paper analyzes the determinants behind the spatial distribution of the sex industry in Thailand. We relate the development of the sex industry to an early temporary demand shock, i.e., U.S. military presence during the Vietnam War. Comparing the surroundings of Thai military bases used by the U.S. army to districts close to unused Thai bases, we find that there are currently 5 times more commercial sex workers in districts near former U.S. bases. The development of the sex industry is also explained by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…29 Similarly, we show that proximity to a mission decreases the likelihood of being in a monogamous relationship, but also decreases the number of sexual partners other than spouse or the number of sexual partners over the lifetime. This is consistent with a pattern of more isolated sexual networks in polygamous structures that are Brodeur et al (2017) show that the concentration of sex workers in few red-light districts in Thailand during the Vietnam war may explain the outbreak of the HIV epidemics in these areas in the early 1990s. associated with lower HIV prevalence (as explained in section 2).…”
Section: Sexual Behaviorssupporting
confidence: 85%
“…29 Similarly, we show that proximity to a mission decreases the likelihood of being in a monogamous relationship, but also decreases the number of sexual partners other than spouse or the number of sexual partners over the lifetime. This is consistent with a pattern of more isolated sexual networks in polygamous structures that are Brodeur et al (2017) show that the concentration of sex workers in few red-light districts in Thailand during the Vietnam war may explain the outbreak of the HIV epidemics in these areas in the early 1990s. associated with lower HIV prevalence (as explained in section 2).…”
Section: Sexual Behaviorssupporting
confidence: 85%
“…We observed that the majority of sex workers had few visits from military clients, with highwaybased workers reporting seeing the highest number of these clients. Historically conflict, and therefore military presence, has created growth in demand for sex work (see for example, Brodeur et al, 2018;de Wildt, 2019). Our results do not illustrate a large increase of sex work demand in the city by military personnel at the time of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Jones and Gong (2019) above, Robinson and Yeh (2011) find that FSWs had sex in the days following illness to another household member or recovering from an STI (both temporary negative shocks) which can be interpreted as evidence for utilisation of the transactional or commercial sex markets 40 . Brodeur, Lekfuangfu, and Zylberberg (2018) examined how the 37 The authors based this on the hypothesis that drought differentially effects genders in rural and urban locations. Thus there are no direct estimates within this study extracted for this review.…”
Section: Transactional Sex and Other Extensive Margin Outcomesmentioning
confidence: 99%